Are we Giving Sufficient Protein in Parenteral Nutrition Support? A Cross-sectional Study on Adult Patients in Intensive Care Units - Fong, Pui Wun Fiona; Saedon, Mahmud Majdi bin Mahmud; Bangguan, Stella Caroline J (Journal of Pharmacy Practice and Community Medicine)
Protein plays a significant role in nutritional support, especially for patients at intensive care unit (ICU) who commonly suffer from net loss of protein. ASPEN and ESPEN guidelines recommend a minimum protein of 1.2g/kg/day for ICU patients; Kidney Disease: Improving Global Outcomes (KDIGO) recommends 0.8g/ kg/day for chronic kidney disease (CKD) stage 4 to 5. This study aimed to determine whether adequate protein was given to adult ICU patients and identify the factors for discrepancy in local settings. A cross sectional study including all adult ICU patients receiving parenteral nutrition (PN) in Hospital Queen Elizabeth (HQE) and HQE II was conducted from January 2018 to April 2019. Relevant information was obtained from patients’ pharmacotherapy review forms. For patients receiving PN and enteral nutrition (EN) concurrently, protein from both sources was accounted for. Among the 52 patients, majority were male (n=41; 78.8%) with median age of 52 years old (IQR=34.5). Median duration of PN support was 6 days (IQR=6.3), and gastrointestinal perforation was the most common indication (n=11; 21.2%). All 45 non-CKD patients (86.5%) received minimum recommended protein of 1.2g/kg/day. Ten patients (19.2% out of 52) who received PN and EN concurrently received a higher average protein up to 1.5g/kg/day. Out of 7 patients (13.5%) with underlying CKD stage 4 to 5, two (3.8% of total 52 patients) received insufficient protein below 0.8g/kg/ day due to restriction of fluid (ROF). Majority of the patients received sufficient protein as per guidelines. In real-life practice, discrepancy may occur due to the fixed-content formulations of commercial PN bags.
Keywords: Protein; Adult; Parenteral Nutrition; Nutrition Support; Intensive Care Unit